Masjid Bersejarah di Jakarta - Jumroni Jumroni (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2006)
In Jakarta, there are many historic buildings which are protected by law became regardedas a live monument and culture preserved. Some of them are old Masjids which are established in pre-colonial era, colonial, and post independence.